Outbreak of Cholera in Tilathi VDC Saptari Nepal - Yadav, DK; Tamrakar, D; Baral, R; Jha, P; Gautam, S; Pokharel, PK (Kathmandu University Medical Journal, 2014)
Background On 2011, Cluster of cholera cases was reported in the Tilathi VDC of Saptari, Nepal. Objective The outbreak was investigated to identify the etiological agent and possible source of infection and guiding the prevention and control measures. Methods Demographic and clinical details were collected from the suspected case-patients, and the outbreak was described by time, place, and person. Focus group discussion and Key informant interview were conducted to assess the practice of sanitation, source of drinking water and probable cause of diarrheal disease. Five stool samples and 10 water samples of tube well and ponds were collected and microbiological study was done in BPKIHS Dharan. Results A total of 111 persons suffered with diarrhea and 02 died of it (attack rate 3.05%, case fatality rate 1.8%). All age groups were affected with disease (median age 26 yrs) and males were affected more than females. Descriptive epidemiology suggested the clustering of cases were around the pond where they clean utensils, take bath and wash clothes. The Vibrio cholerae 01 El Tor, Ogawa serotype was isolated in 03 out of 05 suspected stool samples and in all three of the pond water samples. They reported that most of the houses do not have the toilet and people do not wash their hands regularly with soap and water after defecation. Conclusion Vibrio cholerae was the causative agent behind the outbreak and probable source of infection was the problematic pond water which they used for different purpose. Immediate chlorination of the pond was recommended to halt further spread of the epidemics. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10992 Kathmandu Univ Med J 2012;10(4):36-39